Customer Repeat Purchase Attributes: A Case Of Tapak Urban Street Dining / Joesri Mohamad Saber... [et al.] - Mohamad Saber, Joesri; Raja Mustapha, Raja Iskandar Putera; Ibrahim, Mohd Zool Fadli; Salim, Azlan; Abdul Razak, Mohamad Akmal (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The food truck industry has become a phenomenon and gained popularity around the world. Long gone are the days where street food is only restricted to hotdogs and burgers; the advent of food trucks, brings a mixture of complex menu items and crowd favorites direct to the masses. In Malaysia, food truck influences the social and cultural environment, also providing economic opportunities for the society. Conventional thinking of how a Food and Beverage outlet should be has been traded with a more contemporary idea that includes having a sort of a food truck bazaar where a number of various food trucks are placed to appeal to all crowds. TAPAK Urban Street Dining Kuala Lumpur is one example, where it is a dedicated area for food trucks to sell gastronomic delights of local, western and oriental cuisines. The purpose of this paper is to identify the attributes influencing the repeat purchase of customers at this new dining haven. This study focuses on three major attributes of dining experience in term of food quality, price and service quality. A descriptive research design being applied in this study using quantitative approach. The sample population were selected from the patrons during happy hours and 380 questionnaires were successfully collected. The findings revealed that all attributes suggested has significant relationships with customers’ repeat purchase from the food trucks, providing a better understanding on the food truck concept in Malaysia and how to promote repeat purchases